Synthesis of Cell‐Penetrating S‐Galactosyl–Oligoarginine Peptides as Inducers of Recombinant Protein Expression under the Control of lac Operator/Repressor Systems1. Issue 7 (23rd May 2013) - Mizuta, Yukina; Takasu, Akinori; Higuchi, Masahiro
Abstract The synthesis of glycodendrimers and glycopoly(oxazoline)s as inducers of recombinant protein expression has recently been reported; however, these compounds induced the expression of only small amounts of the green fluorescence protein (GFP), which was used as the model recombinant protein, because of their poor ability to penetrate the Escherichia coli cell membrane. Therefore, S‐galactosyl–oligo(Arg) conjugates have now been synthesized to overcome this problem. Following in vivo expression of GFP induced by each of the S‐galactosyl (Arg)n constructs (n=5, 6, 8) at the T5 promoter in E. coli for 18 hours, we visually observed that the cultures fluoresced green light when excited with UV light. The fluorescent intensities for these cultures were greater than that found for a control culture, which indicates that the peptides had induced GFP expression. Quantitative fluorescent measurements also supported the observations that the peptides were better inducers of GFP expression than the galactosyl dendrimers and the poly(oxazoline)s and the natural inducer lactose. Because the level of GFP expression was directly related to the number of arginine moieties in each peptide, we propose that the number of arginine moieties is responsible for how well each peptide passes through the E. coli membrane, which affects the expression level. A similar tendency was observed when the T7 promoter was placed upstream from the gene for an artificial extracellular matrix protein and the S‐Gal–oligo(Arg) peptides were used as inducers. To assess how the distance between two galactosyl moieties as well as how the multivalent effect (cluster effect) in an oligo(Arg) inducer affects the expression level of GFP, we synthesized a conjugate of Lys(Arg)8 (Lys=lysine) and two S‐galactosyls, which enhanced the expression of GFP in comparison with that obtained for S‐Gal(Arg)8.